Retrospective Analysis of Aseptic Meningitis in Kikuchi–Fujimoto Disease - Cheng R; Lin F; Lu M (Journal of Inflammation Research)
Ran Cheng,1,* Fei Lin,1,* Ming Lu2 1Department of Infectious Diseases, Peking University Third Hospital, Beijing, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, Peking University Third Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ming Lu, Department of Respiratory and Critical Care Medicine, Peking University Third Hospital, Beijing, People’s Republic of China, Email luming197954@163.comIntroduction and Objectives: Kikuchi–Fujimoto disease (KFD) is self-limiting, has an unknown origin, and predominantly affects the lymph nodes. KFD with aseptic meningitis is rare and diagnostically challenging. This retrospective observational study aimed to elucidate the clinical features and treatment outcomes of KFD, particularly in cases with aseptic meningitis.Methods: We conducted this retrospective study to describe KFD to determine the characteristics of the disease, with a particular focus on cases involving aseptic meningitis.Results: Our study comprised 103 patients (33 men, 70 women) diagnosed with KFD at Peking University Third Hospital between January 2013 and March 2024. Diagnosis was based on histological examination of lymph node biopsies. The mean age was 25 (range: 16– 66) years. Clinical manifestations included fever (100%), cervical pain (79.6%), fatigue (49.5%), headache (44.7%), myalgia (26.2%), and hepatosplenomegaly (23.3%). Biological signs included leukopenia (66.0%) and elevated lactate dehydrogenase (> 250 U/L, 83.5%) and ferritin (> 300 ng/mL, 44.6%) levels. Forty-three cases improved with nonsteroidal anti-inflammatory drugs (NSAIDs) as monotherapy, whereas 24 required corticosteroid therapy. Four of the 46 patients with headache underwent cerebrospinal fluid analysis, confirming aseptic meningitis. Notably, all four responded well to nonsteroidal anti-inflammatory drugs.Conclusion: Our findings highlight the features and outcomes of KFD, particularly its association with aseptic meningitis, which has a favorable prognosis in the absence of corticosteroid therapy.Keywords: Kikuchi–Fujimoto disease, aseptic meningitis, histiocytic necrotizing lymphadenitis, self-limiting